ISLAM LIBERAL DAN ANCAMANNYA TERHADAP PEMIKIRAN AHLU AL-SUNNAH WA AL-JAMA’AH - Jufri Naldo (UIN Sumatera Utara, 2019)
ABSTRACTLiberal Islam actually offers a new discourse about Islam in Indonesia, which is packaged in a modern, professional, and sustainable manner with the past. But unfortunately the steps they did were not true at all. In Indonesia the idea of Liberal Islam was examined by Dr. Greg Barton (1998) written in his doctoral dissertation at Monash University, Melbourne, Australia. Research was emphasized from 1960 to 1990. This movement and thought had been influenced at the level of diversity, social and political.Keywords: liberal, ahlus sunnah wal jama'ah